2023
DOI: 10.1371/journal.pone.0271666
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for Human Immunodeficiency Virus (HIV) infection in entrants and residents of an Ethiopian prison

Abstract: Background Prisoners generally have a higher prevalence of HIV infection compared to the general population from which they come. Whether this higher prevalence reflects a higher HIV prevalence in those entering prisons or intramural transmission of HIV within prisons or both is unclear. Any of these possibilities would increase the prevalence found in resident prisoners above that in the general population. Moreover, comparisons of HIV prevalence in entrants and residents and in men and women in African priso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Other studies have reported a numerator of the number of persons testing for HIV during a 6-to-12 month period and a denominator of the average daily census that does not account for the in and out flow of correctional facility populations; these studies have reported testing that reached between 39% and 84% of a population depending on the study design and available testing resources. 12,13,[27][28][29] Several studies have also reported on ART initiation or retention on ART after initiation, reporting between 48% and 98% of persons diagnosed with HIV initiating ART. 22,27,28,30,31 Our estimate of the proportion of people known to be living with HIV on ART of 56%-60% in South Africa and 68% in Zambia is at the lower end of range for ART initiation from these prior studies but may better reflect true ART coverage in correctional settings.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a numerator of the number of persons testing for HIV during a 6-to-12 month period and a denominator of the average daily census that does not account for the in and out flow of correctional facility populations; these studies have reported testing that reached between 39% and 84% of a population depending on the study design and available testing resources. 12,13,[27][28][29] Several studies have also reported on ART initiation or retention on ART after initiation, reporting between 48% and 98% of persons diagnosed with HIV initiating ART. 22,27,28,30,31 Our estimate of the proportion of people known to be living with HIV on ART of 56%-60% in South Africa and 68% in Zambia is at the lower end of range for ART initiation from these prior studies but may better reflect true ART coverage in correctional settings.…”
Section: Discussionmentioning
confidence: 99%